Strings in AdS 4 × ℂℙ3, Wilson loops in NN = 6 super Chern-Simons-matter and bremsstrahlung functions - Aguilera Damia, Jeremías (2014)
We find 1/6 BPS string configurations in AdS 4 × ℂℙ3, which we identify as the duals of certain 1/6 BPS circular Wilson loops in NN = 6 super Chern-Simons-matter gauge theory. We use our results to verify -in the strong coupling limit- a proposal made in arXiv:1402.4128 for a relation between the expectation value of these Wilson loops and the Bremsstrahlung function from deforming 1/2 BPS Wilson lines with a cusp. We also derive an analogous relation between the expectation value of some particular 1/12 BPS Wilson loops and the Bremsstrahlung function from deforming 1/6 BPS Wilson lines with an internal space cusp.